(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the role of linguistics and cognitive linguistics in modern linguistics, focusing on their interrelation and the study of language in close connection with human cognition and mental processes. Cognitive linguistics differs from traditional linguistic approaches by analyzing linguistic units through perception, conceptualization, and categorization processes. The study highlights the importance of the cognitive approach in the development of modern linguistics and discusses the role of key notions such as concept, frame, and mental model in linguistic analysis.